East Java Contingent Training Methods to Win Medals in Kabaddi Sports at PON XXI Aceh – North Sumatra 2024 - Abraham Johns Evangelista; Pudjijuniarto Pudjijuniarto; Heri Wahyudi; Himawan Wismanadi (International Journal Labs, 2025)
Kabaddi is a sport that originated in India. It is the only combat sport in which an individual attacker faces a group of defenders. Kabaddi first became known to the Indonesian public in 2008. Since then, Kabaddi has grown increasingly popular and developed in Indonesia. To achieve success and high performance in Kabaddi, good physical fitness is essential. Therefore, it is important for coaches to use effective training methods to improve the performance of Kabaddi athletes. PON XX1 Aceh - North Sumatra 2024 is a prestigious national event held every four years and serves as a benchmark to assess the development and achievements of each sport in each province. At PON XX1 Aceh – North Sumatra 2024, the East Java Kabaddi team won two bronze medals. This study aims to examine and evaluate the effectiveness of the training methods used by the East Java Kabaddi team in their preparation and performance for PON XX1 Aceh – North Sumatra 2024. The research method employed was a qualitative biographical approach, with the main subject being Abraham Johns Evangelista, who won two bronze medals in the Seven For Five and National Style categories. The training program consisted of nine weekly sessions, each lasting 90–120 minutes, over a period of three months. The results showed several shortcomings in the training methods used by the East Java team. However, despite these issues, this structured and comprehensive training approach enabled the East Java Kabaddi team to secure two bronze medals. This article discusses the importance of appropriate training methods for achieving success and offers recommendations for further developing the training program to attain success in future Kabaddi competitions.